Regimes of Historicity of the Cyprus Conflict in Media Discourses - Trimithiotis, Dimitris; Milioni, Dimitra L.; Spyridou, Lia Paschalia (My University, 2025)
This chapter examines the regimes of historicity that are used for the media construction of the Cyprus conflict—the various rational ways of relating to the past, present, and future. In this study, the present is defined as the varying investments actors make within the course of everyday life, which are based on their interpretations of the complex interrelations between the space of experience (the past) and the horizon of expectation (the future). The objective is to scrutinize the various “pasts” as constructed by the Greek–Cypriot media in order to normalize their portrayals of the present and the future of the Cyprus conflict. The study is based on a corpus of news reports delivered between 1998 and 2017 by five mainstream newspapers of different political identities. The chapter stresses the predominance of the past in the construction of the regimes of historicity of the Cyprus conflict—pastism. It shows how Greek–Cypriot media underline the importance of remembering the past as a precondition for the management of the Cyprus conflict and discusses three differing modes of this regime of historicity. The chapter also argues that the regimes of historicity of the Cyprus conflict comprise fundamental discursive processes for the Greek–Cypriot media, in the sense that the portrayals of other current events of a given period are constructed in accordance with and are used to re-actualize this fundamental media construction of the Cyprus conflict.